Analisis Kesesuaian Ekspektasi dan Kenyataan Pengguna Bumble Dalam Membangun Hubungan - Shofiyah, Nada; Hendrayani, Yani; Ayuningtyas, Fitria (Mahesa Research Center, 2025)
The Bumble app, with its key feature of giving women control over initiating conversations, has become popular among teenagers and adults as a new way to find partners. This study aims to analyze the alignment of expectations and experiences of users of the Bumble dating app, based on the social penetration theory framework. This research method uses descriptive qualitative methods through interviews and observations, examining factors influencing user motivation, such as effectiveness, efficiency, accessibility, and ease of use, as well as challenges faced. The results indicate a gap between user expectations and the reality of Bumble usage. While issues such as identity theft, ghosting, security threats, and shallow communication contribute to a less-than-desirable user experience, enhanced features that provide more options for women have been shown to increase feelings of safety, comfort, and happiness. For online dating apps to better serve their users' needs